Pathophysiological basis of specific immunotherapy - Jutel, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Specific allergen immunotherapy restores normal peripheral tolerance, which appears in healthy individuals. The basic role in this process is played by allergen specific T cells. The shift of functional phenotype of specific T cells results from the suppression and following reactivation step. The suppression of specific T cells is due to the activation of allergen specific regulatory CD4+CD25+ T cells. Cytokines produced by particular population of lymphocytes play the basic role in the regulation of immunoglobuline synthesis and activation of effector cells. Thus SIT modulates both humoral and cellular component of allergic inflammation.